Leveraging Artificial Intelligence and Digital Technologies to Enhance Sociolinguistic Competence and Arabic Language Skills (International Forum of Researchers and Lecturers, 2025)
Artificial Intelligence (AI) and digital technologies have revolutionized language education, providing new opportunities to enhance sociolinguistic awareness and Arabic language skills, including listening, speaking, reading, and writing. This study explores how AI-driven applications and digital platforms support learners in understanding and using various Arabic dialects alongside Modern Standard Arabic. The study uses a qualitative approach to analyse how these technologies bridge the gap between theoretical knowledge and practical communication. The study focuses on tools such as interactive chatbots, speech recognition systems, assistive technologies, virtual assistants, and language learning platforms. These tools align with the Common European Framework of Reference (CEFR) for Languages 2020 and Sustainable Development Goals 4 (SDG 4), highlighting their potential to promote inclusive and equitable language education. The study analyses how AI and digital tools contribute to Arabic learning and enhance communicative competence rather than involving testing or experiments. The findings suggest that these technologies offer significant potential for improving language proficiency and addressing diverse learners' needs.